Deployment of Ultrafiltration for Concentrating and Purification of Antigens - A. V. Komissarov; Yu. A. Aleshina; O. V. Gromova; A. K. Nikiforov; S. A. Eremin; O. A. Volokh; O. A. Lobovikova; A. I. Perepelitsa (Проблемы особо опасных инфекций, 2015)
Represented is domestic and foreign literature review dedicated to usage of ultrafiltration for concentrating and purification of antigens. Discussed are the issues of deployment of various ultrafiltration techniques. It is determined that filtering in the tangential mode by means of modules with flat-frame filtering elements is among the prospective ones. Demonstrated is the impact of such technological specifications as concentration rate, pressure, temperature, and membrane nominal cut-off on molecular mass on the quality of target products, the time elapsed, and preparation losses decrease (increase). Literature data analysis proves to be useful for the selection of the proper procedure for concentrating and purification of protective antigens of bacterial and viral origins. In addition, it allows for taking into account the parameters under discussion when developing specific manufacturing technologies for diagnostic and preventive medical immunobiological preparation production.